Identifikasi Mikroplastik Poliamida (PA) dengan Menggunakan Metode Ekstraksi Penambahan Wet Peroxide Oxidation (WPO) - Safitri, Aprilliana; Dewata, Indang (MASALIQ, 2024)
Microplastics are synthetic solid particles or polymer matrices, with regular or irregular shapes and with sizes ranging from 1 μm to 5 mm. The impact of microplastics is very dangerous for living creatures and the natural environment. The results of microplastic separation using this method were optimal at an oven time of 12 hours, H2O2 concentration of 35% and Characteristics of functional groups using FTIR show that there is absorption of NH, CH, C=O and CN at wavelengths 3292.96, 2934.25, 1631.50, 1538.56 which are characteristic wavelengths for polyamide (PA) microplastics.